Significant Factors Influencing Quality Assurance Practices in Small and Medium-Sized Construction Projects in South Africa - Nyakala, Kgashane Stephen; Munyai, Thinandavha Thomas; Pretorius, Jan-Harm; Vermeulen, Andre (Journal of Economics and Behavioral Studies, 2019)
Although implementing quality assurance (QA) processes in construction play an important role in the South African economy has been acknowledged. However, constructions SMEs are faced with difficulties in improving rural road infrastructure and high-quality roads. Additionally, past research has failed to reach consensus on the construction process and socioeconomic settings in previously disadvantaged areas in South Africa, including the factors influencing negatively the performance of such factors. This research examines what factors facilitate or inhibit the success of construction SMEs and what actions can be taken to being distressed construction SMEs under control. The study adopted a quantitative research approach in which a three-section questionnaire was administered to 160 purposively chosen road- building experts in a South African construction SMEs. The questionnaire was structured into three parts, which sought the participants’ profile, identified the quality assurance practices (QAPs) incorporated in the construction SMEs’ road building programmes, and identified the factors that negatively influence the implementation of QA processes. Data was analysed using the Statistical Package for the Social Sciences (SPSS) version 22. Furthermore, to determine the reliability of the various constructs, mean scores, descriptive statistics and standard deviations were obtained. The empirical findings established eight QAPs that were reliable and valid for implementation processes that can control or minimise their causes of poor quality in projects undertaken by construction SMEs, level of skill acquisition; project planning and control techniques; project construction design; process implementation and process improvement; financial management; organisational structures; involvement of people; and quality standards and measurements. The eight factors attained high Cronbach Alpha values above the recommended 0.70 which indicates high internal consistencies among the sub-scales. Findings from this study should be useful to managers in similar environments may use the results of this study as either diagnostic tools or as a reference benchmark for strategic interventions in solving construction projects related problems. Furthermore, the researchers also recommend that these practices are for quality assurance in construction projects undertaken by SMEs in South Africa.